Profitability of the cow-calf operation business of local peranakan ongole (PO) cattle based on the cow performance and calf price - Rini Widiati; Tri Anggraeni Kusumastuti (Livestock and Animal Research, 2022)
Objective: This study aims to determine the cow-calf operation business performance of the local PO cow that can give better profitability for farmers.Methods: The multistage purposive sampling method was used to determine of the samples. The technique of data collection was carried out using a survey method through direct interviews using a structured questionnaire to 90 beef breeders as respondent with 90 heads of productive PO local cows in Special Region of Yogyakarta. The method of analysis to determine the production performance of cows using descriptive statistics in the form of average and standard deviation. Furthermore, profitability is calculated in the form of net cash farm income with enterprise budgeting analysis.Results: In the current condition, the cow calf operation (CCO) business of PO cattle generated positive net cash farm income. The results of the sensitivity analysis showed that CI and calf weight were sensitive to net cash farm income. In order to get an increase in net cash farm income that was better than the current condition, it is necessary to direct the adoption of technology to shorten the calving interval to 13 months and increase the selling body weight of calves above 150 kg at the age of 6 months.Conclusions: The CCO business of the local PO in the current condition has positive generate income. An increase in income that is better than the current condition can be obtained through technology adoption to shorten the CI and increase the calf sale weight.